Role of Ectoparasites and Rodents in the Spread of Infectious Diseases Infectious Diseases in the Republic of Guinea (International Journal of Scientific Research and Management (IJSRM), 2024)
Parasites are organisms that adversely affect their host, either by modifying specific physiological functions or by multiplying and developing large populations within their host. The aim of this study is to demonstrate the role of ectoparasites of zoonotic rodents in the transmission of infectious diseases. 200 H.B. Sherman type traps, with dried fish as bait, were used to capture rodents, either in lines or spaced 4 metres apart. Rodents were identified using the classic method of Rosevear, D.R., Wilson, D.E. and Reeder, D.M. PCR and RT-PCR were carried out on samples of blood, organs, mite shreds and insects. The study took place from April 2020 to August 2022; 8 prefectures were chosen according to their ecosystems (scrubland, agricultural fields, villages, orchards, bushes, warehouses, riverbanks, etc.). A total of 1,265 rodents, divided into 18 species, were the subject of our work. The species most frequently encountered were: Rattus rattus (n=437), Mus musculus (n=185), Mus spp. (n=150) and Cricetomys gambianus (n=92). A total of 412 ectoparasites were identified, comprising 7 species including 3 mites and 4 insects. Analyses detected 2 cases of Mammarenavirus lassa, 42 cases of Borrelia spp. 5 cases of Anaplasma spp. 4 cases of Ehrlichia spp. 4 cases of Leptospira spp. and 1 case of Coxiella burnetii. Analysis of the results shows that N’Zérékoré and Kindia are the prefectures most at risk.